2017
DOI: 10.1158/2326-6066.cir-17-0292
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent PD-1 Blockade Negates the Effects of OX40 Agonist Antibody in Combination Immunotherapy through Inducing T-cell Apoptosis

Abstract: Combination therapies that depend on checkpoint inhibitor antibodies (Abs) such as for PD-1 or its ligand (PD-L1) together with immune stimulatory agonist Abs like anti-OX40 are being tested in the clinic to achieve improved antitumor effects. Here, we studied the potential therapeutic and immune effects of one such combination: Ab to PD-1 with agonist Ab to OX40/vaccine. We tested the antitumor effects of different treatment sequencing of this combination. We report that simultaneous addition of anti-PD-1 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(86 citation statements)
references
References 35 publications
2
80
3
1
Order By: Relevance
“…Although anti-PD-1 or anti-PD-L1 antibodies are an obvious combination partner for a cancer vaccine, recent preclinical data suggest that optimal sequencing of these therapies may be critical for achieving maximal antitumor activity. In the lymphocytic choriomeningitis virus (LCMV) model, abrogation of the PD-1 pathway led to impaired formation of LCMV-specific memory T cells while the addition of PD-1 inhibition to a regimen of combined OX-40 agonistic and a peptide vaccine in the human papillomavirus-associated tumor model TC-1 compromised efficacy and led to apoptosis of tumor-infiltrating vaccine-specific T cells (43,44). These data indicate that a cancer vaccine may be most effective if administered prior to initiation of PD-1 pathway inhibition.…”
Section: Perspectivementioning
confidence: 99%
“…Although anti-PD-1 or anti-PD-L1 antibodies are an obvious combination partner for a cancer vaccine, recent preclinical data suggest that optimal sequencing of these therapies may be critical for achieving maximal antitumor activity. In the lymphocytic choriomeningitis virus (LCMV) model, abrogation of the PD-1 pathway led to impaired formation of LCMV-specific memory T cells while the addition of PD-1 inhibition to a regimen of combined OX-40 agonistic and a peptide vaccine in the human papillomavirus-associated tumor model TC-1 compromised efficacy and led to apoptosis of tumor-infiltrating vaccine-specific T cells (43,44). These data indicate that a cancer vaccine may be most effective if administered prior to initiation of PD-1 pathway inhibition.…”
Section: Perspectivementioning
confidence: 99%
“…The order of combination of several immunotherapeutic agents also appears to be important, at least in some cases. For instance, in , the authors showed that concurrent administration of immunostimulatory OX40 agonist with a PD‐1 checkpoint inhibitor negated the effects of OX40, causing diminished infiltration of CD8+T cells and an overall lower antitumor immune response. However, sequential combination of the two agents, where OX40 administration was followed by anti‐PD‐1 therapy, but not in the reverse order, resulted in significantly improved therapeutic efficacy .…”
Section: Immunometabolismmentioning
confidence: 99%
“…22 However, more recently other studies have reported opposing effects. 23,24 Interestingly, however, a study by Messenheimer et al found that when a-OX40 and a-PD-1 antibodies were administered sequentially by treating MMTV-PyMT tumor-bearing mice with a-OX40 mAb before a-PD-1 mAb, the sequential combination therapy resulted in augmented antitumor efficacy. 23,24 Interestingly, however, a study by Messenheimer et al found that when a-OX40 and a-PD-1 antibodies were administered sequentially by treating MMTV-PyMT tumor-bearing mice with a-OX40 mAb before a-PD-1 mAb, the sequential combination therapy resulted in augmented antitumor efficacy.…”
Section: Using Immunomodulatory Antibodies To Enhance Car T-cell Antimentioning
confidence: 99%
“…Two different studies reported that the concurrent addition of a-PD-1 mAb markedly reduced the therapeutic response of a-OX40 mAb. 23,24 Interestingly, however, a study by Messenheimer et al found that when a-OX40 and a-PD-1 antibodies were administered sequentially by treating MMTV-PyMT tumor-bearing mice with a-OX40 mAb before a-PD-1 mAb, the sequential combination therapy resulted in augmented antitumor efficacy. However, this improved effect was not observed when a-PD-1 mAb was administered before a-OX40 mAb, highlighting the importance of timing and sequence of such treatments.…”
Section: Using Immunomodulatory Antibodies To Enhance Car T-cell Antimentioning
confidence: 99%